Involvement of astroglial glutamate–glutamine shuttle in modulation of the jaw‐opening reflex following infraorbital nerve injury. (25th March 2014) - Mostafeezur, Rahman Md.; Shinoda, Masamichi; Unno, Syunpei; Zakir, Hossain Md.; Takatsuji, Hanako; Takahashi, Kojiro; Yamada, Yoshiaki; Yamamura, Kensuke; Iwata, Koichi; Kitagawa, Junichi
Abstract To evaluate the mechanisms underlying orofacial motor dysfunction associated with trigeminal nerve injury, we studied the astroglial cell activation following chronic constriction injury (CCI) of the infraorbital nerve (ION) immunohistochemically, nocifensive behavior in ION‐CCI rats, and the effect of the glutamine synthase (GS) blocker methionine sulfoximine (MSO) on the jaw‐opening reflex (JOR), and also studied whether glutamate–glutamine shuttle mechanism is involved in orofacial motor dysfunction. GFAP‐immunoreactive (IR) cells were observed in the trigeminal motor nucleus (motV) 3 and 14 days after ION‐CCI, and the nocifensive behavior and JOR amplitude were also strongly enhanced at these times. The number of GS‐ and GFAP‐IR cells was also significantly higher in ION‐CCI rats on day 7. The amplitude and duration of the JOR were strongly suppressed after MSO microinjection (m.i.) into the motV compared with that before MSO administration in ION‐CCI rats. After MSO administration, the JOR amplitude was strongly suppressed, and the duration of the JOR was shortened. Forty minutes after m.i. of glutamine, the JOR amplitude was gradually returned to the control level and the strongest attenuation of the suppressive effect of MSO was observed at 180 min after glutamine m.i. In addition, glutamine also attenuated the MSO effect on the JOR duration, and the JOR duration was extended and returned to the control level thereafter. The present findings suggest that astroglial glutamate–glutamine shuttle in the motV is involved in the modulation of excitability of the trigeminal motoneurons affecting the enhancement of various jaw reflexes associated with trigeminal nerve injury.